Evaluation of the Education Plan and Activities of Swiss Sport Integrity. A report of a science-practice co-operation. - Christoffer Klenk; Jonas Personeni (Current Issues in Sport Science, 2025)
Introduction The WADA requires the National Antidoping Organisations (NADOs) to annually evaluate its education plan and activities to accomplish the International Standard for Education of the WADA Code (2021), preferably done in cooperation with an independent external partner from the field of science and research. Therefore, Swiss Sport Integrity (SSI) and Institute of Sport Science (ISPW) entered into a cooperation agreement in 2020 for annual evaluating SSI’s education plan and activities from 2021 to 2024. This contribution aims to reporting the process of such a science-practice cooperation and identifying factors that are critical for effective cooperative evaluation.